Fast procedure for characterization of voltage sag for medium voltage (MV) distribution network without online monitoring using fault and regression analyses - Loo C.K.; Au M.T. (Insight Society, 2023)
Power Quality (PQ) Management undertaken by most utilities including TNB involves monitoring/online measurement, data processing & analysis, reporting and customers' complaints management. The Malaysian regulator requires proactive communication and PQ disturbance report covering specific details such as percentage remaining voltage, duration, and cause of voltage sag/dip events to be shared with affected customers. The above-stipulated requirement can be easily met for substations/exposed areas with online PQ measurements, which capture voltage magnitude and duration that could be corroborated with tripping events. However, it is not practical to have online monitoring facilities as the majority of medium voltage (MV) substations are not equipped with voltage and current transformers where measurements could be tapped. Current procedures of characterizing voltage sag for substations without measurements facilities is time-consuming. In this paper, a fast procedure using combinations of fault simulations and regression analysis to characterize voltage sag is proposed. Extensive results from 160 simulation cases comprising 4 network operating configurations, 20 fault distances, and 2 fault types are used in the regression formulation. The results based on the proposed fast procedure for MV distribution network without online monitoring is found to be fairly accurate.